Monitoring the extracellular matrix remodeling of high‐grade serous ovarian cancer with nonlinear optical microscopy. Issue 6 (3rd March 2021) - Yan, Junshuai; Zhao, Yihua; Lin, Fangrui; Qu, Junle; Liu, Qianyu; Pan, Ying; Liu, Liwei
Abstract: The mortality of high‐grade serous ovarian cancer (HGSOC) accounts for 70% to 80% of all ovarian cancer deaths and overall mortality rate has not declined in the last decade. Recently, many studies have demonstrated that HGSOC originates from the fallopian tubes. The extracellular matrix (ECM) is present in all tissues, its remodeling and interaction with cells are crucial for regulating cell proliferation, migration, and differentiation. In this paper, we used label‐free nonlinear optical microscopy to image tissues of the fallopian tube and ovary. Combining a set of image processing algorithms, we monitored the remodeling of ECM in the fallopian tube and ovary during the invasion of primary serous fallopian tube tumor into the ovary in microscopic dimension. With this approach, we can obtain physiological information of HGSOC at the early stage, which provided useful data for auxiliary clinical diagnosis. Abstract : We used label‐free large‐field TPEF and SHG optical microscopy to image HGSOC tissue sections to obtain the whole invasion path labeled by SHG from primary serous fallopian tube tumor into the ovary. And we combined a set of image processing algorithms consisting of the angle between collagen fiber and tumor epithelium statistics, FFT, GLCM, and SHG and TPEF intensity statistics at ROIs near the fallopian tubes and ovarian epithelium (<400 μm), which can effectively detect the remodeling of the epithelium of fallopian tube and ovary and their surrounding ECM during the invasion route of FTSECs to the ovary.